Phytochemical Profiling, GC-MS Characterization, Antimicrobial, Antioxidant and Antidiabetic Activities of Stem Bark Extracts of Glycosmis pentaphylla (Retz.) DC. - Abdul Shafiulla,; Mahanthesh Kumar G,; Ramesh C K,; Riaz Mahmood, (The Bioscan, 2026)
Background: Glycosmis pentaphylla (Retz.) DC. is a medicinal plant widely used in traditional medicine for the treatment of various ailments. The present study aimed to investigate the phytochemical composition, GC–MS profile, antimicrobial, antioxidant and antidiabetic activities of the stem bark extracts of G. pentaphylla. Methods: Stem bark extracts were prepared using chloroform, ethyl acetate, methanol and aqueous solvents. Qualitative phytochemical screening was performed using standard procedures. Total phenolic content (TPC) and total flavonoid content (TFC) were determined using the FolinCiocalteu and aluminum chloride colorimetric methods, respectively. GC–MS analysis was conducted to identify major phytoconstituents. Antimicrobial activity was evaluated against Bacillus cereus, Escherichia coli and Candida albicans using the agar well diffusion method. Antioxidant activity was assessed through DPPH and hydrogen peroxide scavenging assays, while antidiabetic potential was evaluated by α-amylase inhibition and glucose uptake assays. Results: Phytochemical screening revealed the presence of alkaloids, phenols, flavonoids, terpenoids, tannins, glycosides, sterols, saponins and carbohydrates in varying proportions among the solvent extracts. The aqueous extract exhibited the highest total phenolic content (68.20 ± 0.01 mg GAE/g extract) and total flavonoid content (59.01 ± 0.05 mg QE/g extract), followed by the methanolic extract. GC–MS profiling identified β-myrcene, β-pinene and sabinene as major volatile constituents, while vitexin was recognized as an important non-volatile flavonoid phytoconstituent. The stem bark extract demonstrated concentration-dependent antimicrobial activity against B. cereus, E. coli and C. albicans. Furthermore, the extract exhibited appreciable antioxidant activity and significant α-amylase inhibitory and glucose uptake activities, indicating promising antidiabetic potential. Conclusion: These findings demonstrate that Glycosmis pentaphylla stem bark is a rich source of bioactive phytochemicals with antimicrobial, antioxidant and antidiabetic activities. The observed biological effects may be attributed to the synergistic actions of phenolic compounds, flavonoids and terpenoid constituents. These results support the traditional medicinal use of this plant and highlight its potential for the development of novel phytopharmaceutical agents.